Effect of Operating Costs on Profit at PT. Indonesian Port I (Persero) Medan - Novien Rialdy (AIBPM Publisher, 2019)
Every company engaged in business has the main goal in establishing a business that is profit as much as possible because profit as a measuring tool used to assess the success or failure of the company in carrying out work activities in the field of production and services. Profit is very important for the company, so important the management of the company always tries to make good plans so that the process of work activities continue to run and obtain the desired results. In terms of earning profit as much as possible, it is inseparable from the factors that are related and very influential in increasing the profits that will be obtained by the company such as in general income and costs. The costs referred to in this study are company operating costs, because PT. Pelabuhan Indonesia I (Persero) Medan is a company engaged in port services which all costs incurred are operating costs. Operating costs is one that reduces the value of corporate profits so that to achieve the set profit target it is necessary to know the magnitude of the increase in operating costs beforehand, for which the company needs to plan decisions in determining its operating costs. Mangingat the importance of operating costs in achieving the target of achieving profit, the author examines the Effect of Operating Costs on Profit at PT. Indonesian Port I (Persero) Medan. This research aims to find out how much influence the operating costs have on profit at PT. Pelabuhan Indonesia I (Persero) Medan, where the growth rate of operating costs is quite high. While the benefits obtained are enriching the theory for the company in solving problems that occur about operating costs and profits, and increase knowledge and broaden the writer's insight regarding operating costs that have an influence on profits From the research it is known that operating costs and profits tend to increase every year. This can be seen from the results of t-test calculations, obtained a value of 2.07. When compared with t table for critical area 3 (dk = 5-2 = 3) with a level of 0.05% of 2.353. From the results of t arithmetic = 3 then it is shown at t table 2.353 for a normal (standard) environment that it can be proved that t count is smaller than t table (2.07